Immunodetection of Adhesin Pili Protein 38.6 kDa K. pneumoniae Using Western Blot - Dini Agustina; Diana Chusna Mufida; Nurul Indah Saffanah (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2021)
Abstract: Klebsiella pneumoniae is a pathogen that causes infections in communities and hospitals. These bacteria have many virulence factors that play an important role in the pathogenicity of infection and antibiotic resistance. Pili protein Klebsiella pneumoniae with 38.6 kDa as one of the virulence factors, that have roles as hemagglutinin dan adhesin protein so potentially as a vaccine candidate. This research aimed to immunodetection pili protein 38.6 kDa using Western Blot. Western Blot was used to detect that protein with specific primary antibodies. These antibodies are obtained from mice serum-induced intraperitoneally with Pili protein 38.6 kDa Klebsiella pneumoniae. Protein bands that appear on the membrane of Western Blot results are proteins with a molecular weight of 85.6 kDa, 65.5 kDa, 46.9 kDa, and 29.4 kDa. This study concludes that Pili protein 38.6 kDa Klebsiella pneumoniae as the target protein does not appear in the Western Blot result.Abstrak: Klebsiella pneumoniae adalah patogen yang menyebabkan infeksi di komunitas maupun rumah sakit. Bakteri tersebut memiliki banyak faktor virulensi yang berperan penting dalam patogenisitas terjadinya infeksi dan resistensi antibiotik. Protein pili Klebsiella pneumoniae dengan 38,6 kDa sebagai salah satu faktor virulensi, memiliki peran sebagai protein hemagglutinin dan adhesin sehingga berpotensi sebagai kandidat vaksin. Tujuan penelitian ini untuk imunodeteksi protein pili 38,6 kDa dengan menggunakan Western Blot. Western Blot digunakan untuk mendeteksi protein itu dengan spesifik antibodi primer. Antibodi ini diperoleh dari serum tikus yang telah diinduksi secara inteperitoneal dengan protein Pili 38,6 kDa Klebsiella pneumoniae. Band protein yang muncul pada membran hasil Western Blot adalah protein dengan berat molekul 85,6 kDa; 65,5 kDa; 46,9 kDa dan 29,4 kDa. Dari penelitian ini dapat disimpulkan bahwa protein Pili 38.6 kDa Klebsiella pneumoniae sebagai protein target tidak muncul.